The Role of Leadership Style and Information Technology on Employee Performance Mediated by Job Satisfaction in Cargo Companies in DKI Jakarta - Djoko Setyo Widodo (Journal of Global Economic Research, 2025)
The purpose of this study is to determine the effect of leadership style and information technology on employee performance mediated by job satisfaction in cargo companies in DKI Jakarta. The method used is descriptive quantitative. The analysis tool used is SEM SmartPLS 4.1.0.0. The data used is primary data. The population in this study is unknown. The sampling technique used is Simple Random Sampling using Hair's formula. The research was conducted at a cargo company in Jakarta. The tests conducted were Validity Test, Reliability Test, Inner Model, Outer Model, and Hypothesis Test. The results of this study are as follows: 1) Leadership style has a positive and significant effect on employee satisfaction at a cargo company in Jakarta; 2) Information technology has a positive and significant effect on employee satisfaction at a cargo company in Jakarta; 3) Leadership Style does not have a positive and significant effect on Employee Performance in Cargo Companies in Jakarta; 4) Information Technology has a positive and significant effect on Employee Performance in Cargo Companies in Jakarta; and 5) Employee Satisfaction has a positive and significant effect on Employee Performance in Cargo Companies in Jakarta; 6) Leadership style has a positive and significant effect on employee performance through employee satisfaction in cargo companies in Jakarta; and 7) Information technology has a positive and significant effect on employee performance through employee satisfaction in cargo companies in Jakarta.